2000
DOI: 10.1037/0096-1523.26.6.1797
|View full text |Cite
|
Sign up to set email alerts
|

Cue utilization in communication of emotion in music performance: Relating performance to perception.

Abstract: This study describes the utilization of acoustic cues in communication of emotions in music performance. Three professional guitarists were asked to perform 3 short melodies to communicate anger, sadness, happiness, and fear to listeners. The resulting performances were analyzed with respect to 5 acoustic cues and judged by 30 listeners on adjective scales. Multiple regression analysis was applied to the relationships between (a) the performer's intention and the cues and (b) the listeners' judgments and the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
312
1
13

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 275 publications
(352 citation statements)
references
References 80 publications
26
312
1
13
Order By: Relevance
“…Another difference is that the cue-based theory does not consider structural context. Recognition of an emotion depends on an addition of cues; which emotion is recognized depends on which emotion gets most evidence, as in Juslin's adaptation of the Brunswikian lens model (Juslin, 2000). In this summation, the kind of cues may partly depend on participants' (cultural) background, but the interpretation of cues is fixed within a certain context.…”
Section: Emotional Ornamentationmentioning
confidence: 99%
“…Another difference is that the cue-based theory does not consider structural context. Recognition of an emotion depends on an addition of cues; which emotion is recognized depends on which emotion gets most evidence, as in Juslin's adaptation of the Brunswikian lens model (Juslin, 2000). In this summation, the kind of cues may partly depend on participants' (cultural) background, but the interpretation of cues is fixed within a certain context.…”
Section: Emotional Ornamentationmentioning
confidence: 99%
“…These features have certain characteristics that are crucial to understand in order to devise an efficient teaching strategy. Juslin (1995Juslin ( , 2000 suggested that we should use a variant of Brunswik's (1956) lens model to capture the special characteristics of the communicative process, and this model forms the basis of the computer program that we have developed.…”
Section: Brunswik's Lens Modelmentioning
confidence: 99%
“…The redundancy among cues partly reflects how sounds are produced on musical instruments (e.g., a harder string attack produces a tone, both louder and sharper in timbre). (For further evidence and discussion of the lens model, see Juslin, 2000, andLaukka, 2003.) The relationships between the performer's intention, the acoustic cues, and the listener's judgment can be modeled using correlational statistics.…”
Section: Expression Recognitionmentioning
confidence: 99%
“…On se la représente souvent par une alchimie subtile entre épaisseur de grain sonore, reliefs des courbes mélodiques, structuration du phrasé musical, variations dans la rythmique et la richesse des couleurs du timbre. Les musiciens transmettent leur expressivité et les émotions que leur inspirent un texte musical par des variations de ces indices acoustiques [Juslin 2000]. Pour cette raison, l'exécution d'une pièce musicale ne suit quasiment jamais complètement les valeurs nominales écrites dans la partition.…”
Section: Une Question De Variationsunclassified
“…Les notes tendent souvent par ailleurs à être rallongées sur les temps forts et raccourcies sur les temps faibles [Clarke 1985]. Il s'agit là de règles d'interprétation communes aux interprètes, qui soulignent les micro-structures spécifiques et reproductibles du contenu musical [Juslin 2000]. Grâce à ces principes génératifs de l'expressivité, une représentation mentale de la structure musicale peut être encodée au travers des gestes de l'instrumentiste et facilement décodée par l'auditeur [Clarke 1987, Clarke 1988, Clarke 1989].…”
Section: Les Variations Dues à La Structure Musicaleunclassified